"Touching the depths of suffering with others": The nature of witnessing with survivors of torture. Issue 3 (3rd July 2022) - Mighetto, Isabella
ABSTRACT: Torture and exile shatter a person's sense of self, their trust in others, and produce isolation and an array of post-traumatic sequelae. This article explores the experiences of therapists working with torture survivors at a London-based charity. It explores what, for them, constitutes the process of bearing witness to narratives of trauma in therapeutic encounters. An Interpretative Phenomenological Analysis (IPA) was employed, using semi-structured interviews. Analysis was underpinned by intersubjectivity and psychoanalytic social theory. The findings illuminate the significance of engaging in affective relationships of political solidarity and validation against the backdrop of the structural disavowal of the 'hostile environment' in the UK context. Witnessing was described as the interplay of 'staying with' people's trauma without attempting to 'fix' or pathologize. Participants described witnessing multi-dimensional aspects of a person. The article concludes by discussing the implications of witnessing for therapists working with survivors of torture.